2015
DOI: 10.1186/s40064-015-0870-5
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 I148M associations with liver carcinogenesis in Japanese chronic hepatitis C patients

Abstract: AimTo investigate associations between patatin-like phospholipase domain-containing 3 (PNPLA3) genotypes and fibrosis and hepatocarcinogenesis in Japanese chronic hepatitis C (CHC) patients.MethodsTwo hundred and thirty-one patients with CHC were examined for PNPLA3 genotypes, liver stiffness measurements (LSM), and hepatocellular carcinoma (HCC) from May 2010 to October 2012 at Fujita Health University Hospital. The rs738409 single nucleotide polymorphism (SNP) encoding for a functional PNPLA3 I148M protein v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…The data was heterogeneous ( I 2 = 65.9%, P = 0.081), with evidence of publication bias as assessed by Begg-Mazumdar test ( P = 0.036) and tendency for publication bias as assessed by Egger test ( P = 0.059). Sensitivity analysis after excluding studies with lowest[14] and highest[49] OR revealed similar effect size: 1.82 (95%CI: 1.41-2.34) with I 2 = 18.8%, P = 0.30. Additionally, when Dual and Tweedie trim and fall test was used to assess publication bias, 3 studies were trimmed with no change in effect size (OR = 1.39, 95%CI: 1.01-1.92).…”
Section: Resultsmentioning
confidence: 86%
“…The data was heterogeneous ( I 2 = 65.9%, P = 0.081), with evidence of publication bias as assessed by Begg-Mazumdar test ( P = 0.036) and tendency for publication bias as assessed by Egger test ( P = 0.059). Sensitivity analysis after excluding studies with lowest[14] and highest[49] OR revealed similar effect size: 1.82 (95%CI: 1.41-2.34) with I 2 = 18.8%, P = 0.30. Additionally, when Dual and Tweedie trim and fall test was used to assess publication bias, 3 studies were trimmed with no change in effect size (OR = 1.39, 95%CI: 1.01-1.92).…”
Section: Resultsmentioning
confidence: 86%
“…These include genetic factors such as PNPLA3. PNPLA3 rs738409 2 risk alleles has been identified a risk factor for developing HCC associated with NAFLD [ 44 ], alcoholic liver disease [ 45 ] or chronic HCV infection [ 46 , 47 ].The role of central obesity as a risk for HCC is also emerging as shown in a large European study [ 48 ]. The high prevalence of cirrhosis in Hispanics in South Texas seems to correlate with the high prevalence of HCC in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, additional GWAS have identified a nonsynonymous SNP rs738409 (C > G; p. I148M) in patatin‐like phospholipase domain‐containing 3 ( PNPLA3 ) and a SNP rs58542926 (C > T; p. E167K) of transmembrane 6 superfamily 2 ( TM6SF2 ), two genes involved in lipid metabolism, as associated with development of NAFLD . PNPLA3 rs738409 has also been associated with HCC in case–control study and prospective cohorts in alcohol‐related cirrhosis whereas the role in HCC development on HCV related cirrhosis or on NAFLD remains controversial in the literature . TM6SF2 rs58542926 was associated with HCC occurrence in patients with alcoholic cirrhosis but few data were available in other etiologies .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] PNPLA3 rs738409 has also been associated with HCC in case-control study and prospective cohorts in alcohol-related cirrhosis whereas the role in HCC development on HCV related cirrhosis or on NAFLD remains controversial in the literature. [15][16][17][18][19][20] TM6SF2 rs58542926 was associated with HCC occurrence in patients with alcoholic cirrhosis but few data were available in other etiologies. 13,[21][22][23] Moreover, whether these aforementioned variants predispose to HCC developed on a nonfibrotic liver is currently unknown.…”
Section: Introductionmentioning
confidence: 99%